Key Role of Phosphorylation in Small Heat Shock Protein Regulation via Oligomeric Disaggregation and Functional Activation - Zachary B. Sluzala; Angelina Hamati; Patrice E. Fort (Cells)
Heat shock proteins (HSPs) are essential molecular chaperones that protect cells by aiding in protein folding and preventing aggregation under stress conditions. Small heat shock proteins (sHSPs), which include members from HSPB1 to HSPB10, are particularly important for cellular stress responses. These proteins share a conserved α-crystallin domain (ACD) critical for their chaperone function, with flexible N- and C-terminal extensions that facilitate oligomer formation. Phosphorylation, a key post-translational modification (PTM), plays a dynamic role in regulating sHSP structure, oligomeric state, stability, and chaperone function. Unlike other PTMs such as deamidation, oxidation, and glycation—which are often linked to protein destabilization—phosphorylation generally induces structural transitions that enhance sHSP activity. Specifically, phosphorylation promotes the disaggregation of sHSP oligomers into smaller, more active complexes, thereby increasing their efficiency. This disaggregation mechanism is crucial for protecting cells from stress-induced damage, including apoptosis, inflammation, and other forms of cellular dysfunction. This review explores the role of phosphorylation in modulating the function of sHSPs, particularly HSPB1, HSPB4, and HSPB5, and discusses how these modifications influence their protective functions in cellular stress responses.